AUTOMATION of ADJUSTMENT of the EQUIPMENT of RESOURCE TESTS ON the READJUSTED EQUIPMENT - V.; L. ZURAVLEV; U. PONOMAREV (Advanced Engineering Research, 2006)
The   article  describes  the criteria and  algorithms  of  the  automated  adjustment  of  the  equipment  of  resource  tests  of  quickwearing  details  of  the  industrial  equipment.